(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2016)
This contribution originates as part of a preliminary work initiated in the site of Saepinum – Altilia (CB, Molise), which is still waiting for a scientific edition of the excavations, despite the latter having started in the ninety-fifties. It specifically focuses on the macellum building, whose problem-prone aspects are still high in number, such as the fairly relevant issue of establishing chronological phases. With regards to the various secondary issues, though not less interesting, we’d like to draw the attention to a big circle-shaped stone block placed at the heart of the building which is open to several interpretations (water reservoir of a fountain? grinding wheel of a crusher?), in order to examine the various possible solutions to the issue and appreciate how real its belonging to the building is.